Ultrasonographic, endoscopic and histological appearances of the caecum in cats presenting with chronic clinical signs of caecocolic disease. Issue 2 (February 2017) - Hahn, Harriet; Pey, Pascaline; Baril, Aurélie; Charpentier, Julie; Desquilbet, Loic; Le Poder, Sophie; Château-Joubert, Sophie; Laloy, Eve; Freiche, Valerie
Objectives: This study aimed to describe the ultrasonographic, endoscopic and histological characteristics of the caecum and ileocaecocolic junction in cats suffering from chronic clinical signs compatible with caecocolic disease. Methods: Cats presenting with clinical signs suggestive of a caecocolic disease were prospectively recruited. All cats underwent an ultrasonographic examination of the caecum, ileum, colon, ileocolic lymph nodes and local mesenteric fat, in addition to comprehensive abdominal ultrasonography. This was followed by a colonoscopy with a macroscopic assessment of the caecocolic mucosa; caecocolic tissue samples were systematically collected for histologic analysis. Results: Eighteen cats were included. Eleven of 18 cats had ultrasonographic abnormalities adjacent to the ileocaecocolic junction (lymphadenopathy, local steatitis) and 13/18 cats had abnormalities directly related to the junction (wall thickening, loss of wall layering). Seventeen of 18 cats had at least one ultrasonographic abnormality. Endoscopically, hyperaemia, oedema, discoloration and/or erosions were found in all cats. Each cat was classified as having mild or moderate-to-severe lesions according to endoscopic results; no classification could be established statistically for ultrasonographic results. The accentuation of the dimpled pattern tended to be inversely related to the severity of endoscopic lesion scoring. Histologically, a large proportion of cats showed typhlitis (13/16), one had lymphoma and two were normal. All cats with typhlitis also had colitis. There was only slight agreement between endoscopic and histological caecal results regarding the severity of lesions. Loss of caecal wall layering on ultrasound was found in 7/18 cats and, surprisingly, did not appear as a reliable predictor of the severity of inflammation or of malignancy; neither did local steatitis nor lymph node size. Conclusions and relevance: Ultrasonography and endoscopy should not be used as the sole methods to investigate the ileocaecocolic region in cats with clinical signs suggestive of caecocolic disease. The presence of chronic clinical signs should routinely prompt histological biopsy.